Avaliação dos efeitos antitumorais de extratos brutos produzidos por fungos endofíticos isolados de Eugenia jambolana em células de hepatocarcinoma murino (Hepa-1c1c7) - Lopes, Patrícia da Silva [UNESP] (2015)
Hepatocellular carcinoma (HCC) is more frequent primary liver cancer, and third most commum cause of cancer mortality. Among primary liver tumors HCC is responsible for nearly 90% of cases. Compared to search for the development of production of novel drugs from natural products, the endophytic fungi have been presented as promising sources. Recent studies showed that extracts of endophytic fungi have various activities, such as, properties antitumor. The aim of this study was to evaluate cytotoxicity capacity of the crude extract isolated endophytic fungus ripe fruit, Ej-fm1 and unripe fruit, Ej-FV1 Eugenia jambolana in Murine hepatoma cell (Hepa 1c1c7), Human hepatocarcinoma cell line (Hep G2) and spontaneously immortalized human keratinocytes (HaCaT) and check the induction of apoptosis, caspase activity, genotoxic activity, mutagenic and distribution of cell cycle. Our findings indicate that demonstrated that both extracts showed inhibitory activities. The crude extract from Pseudofusicoccum stromaticum (Ej-fm1) possessed more selectivity against Hepa1c1c7 showed IC50, value of 58 μg/mL, having a cellular inhibition 63.4% and 38.4% for the concentration 100μg / ml and 50μg/ml. While for HepG2 and HaCat, no significant cell death. The extract of Neofusicoccum sp.(Ej-fv1) induced high cytotoxicity, showed cellular inhibition 67.83% just at concentration 100μg/ml with IC50 value of 89 μg/mL. HepG2 and HaCaT cell also showed significant inhibition (38.4% and 43.5%, respectively) also only at the highest concentration. To evaluate apoptosis using Hoechst/ Propidium iodide method in Hepa1c1c7 cells, the extract (Ej-fm1) showed statistical difference for presence of late apoptosis, as well as necrosis. But the extract (Ej-fv1) there are significant cell death only in the concentration of 100μg / mL for early apoptosis and necrosis, noting a concentration-response for early apoptosis. About the analyses of cell death mechanisms, we ...